The perception of travellers and the World Heritage Site image - Pavlić, Ivana, ekonomistica (Array, 2020)
The paper investigates the main image determinants of World Heritage Site (WHS) among different types of travellers. The main purpose is to define the main features of different types of travellers (tourists and cruise ship visitors) and to determine the attributes that create their particularly perceived image of WHS. In order to gain the main aims, empirical research, based on questionnaire on randomly–chosen travellers visiting WHS, was carried. The sample consisted of 547 tourists and 472 cruise ship visitors who visited WHS - Old city of Dubrovnik (OCD) in the period April 1st – October 1st 2016. Research spatial framework consists of multiple-use protected area with buffer zone. Explorative factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modelling (SEM) were applied. The results show that there are differences between image formation among different types of travellers regarding cognitive and affective image elements. The obtained results can be used as a base model for investigating the influence of the information sources, socio-demographics and motivation on mediating ones (cognitive and affective evaluation), and finally on the dependent variable of the overall image of the WHS perceived by different traveller categories.